SIMULTAN JANGKA PANJANG ANTARA FLUKTUASI INDEKS HARGA SAHAM, TINGKAT INFLASI, SUKU BUNGA DAN KURS IDR/USD TERHADAP RETURN SAHAM REKSADANA DI INDONESIA - R. Adisetiawan (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
The year 2010 is the year in which the stock market is experiencing a positive development after the financial crisis in 2008, and this research will examine several indicators of macroeconomic phenomena such as the composite stock price Index fluctuation (IHSG ) which is considered to represent market conditions, inflation rates, interest rates on Bank Indonesia Certificates (SBI) and the exchange rate USD/CHF terhadp return mutual fund shares in Indonesia 2000-2014 period. Analysis techniques used in this research was inferensial by the method of multiple regression to predict how far the influence of variables independent of the dependent variable. Before that first test will be done Best Linear Unbiased Estimators (BLUE) to avoid deviation of classical assumptions.The results showed fluctuations in JCI, inflation rates, interest rates and exchange rates to SBI INR/USD affect return mutual fund shares in Indonesia, where the most significant influence is shown by the exchange rate USD/USD.Keywords: JCI, inflation, exchange rates, SBI INR/USD, stock mutual fund return.